Data for "Athabasca River avulsion underway in the Peace-Athabasca Delta, Canada" - Wang, Bo; Kyzivat, Ethan; Colin Gleason; Jessica V. Fayne; Merritt E. Harlan; Theodore Langhorst; Dongmei Feng; Emily Eidam; Daniel L. Peters; Yuta Ishitsuka; Wayana Dolan; Tamlin M. Pavelsky; et al. (Zenodo, 2023)
Water surface elevation, river depth, and ADCP data for paper "Athabasca River avulsion underway in the Peace-Athabasca Delta, Canada, Water Resources Research , Wang et al. 2023".